2022
DOI: 10.3390/vaccines10050724
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Socioeconomic Determinants of COVID-19 Booster Vaccine Acceptance: An Indonesian Cross-Sectional Study

Abstract: Introduction: The threat of new SARS-CoV-2 variants indicates the need to implement COVID-19 vaccine booster programs. The aim of this study was to identify the level of booster acceptance and its determinants. Methods: A cross-sectional online survey was conducted in Jakarta and Bali, Indonesia. Booster acceptance was divided into three categories: non-acceptor, planned acceptor, and actual acceptor. The primary independent variables were health beliefs, media influence, and trust in authoritative sources. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 41 publications
4
42
0
2
Order By: Relevance
“…Our review identified that people with a higher educational level were more likely to accept a booster dose. This finding is confirmed by the literature since an increased educational level is associated with an increased primary COVID-19 vaccine acceptance rate [ 36 , 50 , 51 ]. Well-educated individuals have a higher risk perception of COVID-19 infection, while less-educated people are vaccine-hesitant because they do not think they will be affected by COVID-19 [ 66 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our review identified that people with a higher educational level were more likely to accept a booster dose. This finding is confirmed by the literature since an increased educational level is associated with an increased primary COVID-19 vaccine acceptance rate [ 36 , 50 , 51 ]. Well-educated individuals have a higher risk perception of COVID-19 infection, while less-educated people are vaccine-hesitant because they do not think they will be affected by COVID-19 [ 66 ].…”
Section: Discussionsupporting
confidence: 84%
“…In particular, older individuals were more likely to accept a booster. Evidence supports this finding since increased age is associated with increased COVID-19 vaccination intentions and uptake [ 36 , 41 , 50 ]. The elderly may have a greater sense of responsibility and accountability for themselves and their societies relative to younger individuals.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Subgroup analysis according to the actual vaccination or intention to be vaccinated did not explain this heterogeneity ( Supplementary Figure S1 ). Since six studies represented the COVID-19 vaccine booster dose acceptance as actual vaccination or intention to be vaccinated [ 51 , 54 , 55 , 61 , 66 , 73 ], it was a necessary to identify the pooled proportion for the actual booster dose vaccination and intention to receive the booster dose separately.…”
Section: Resultsmentioning
confidence: 99%